Learning Readiness of Gki Classic Waibumoi Sunday School Children Assessed In Physical And Psychological Conditions - Roragaba, Yeni Irawati; Samuati Banga, Berthin (Lembaga Penelitian dan Pendidikan Mandala, 2024)
development of communication and information. The purpose of this study is to elaborate on the development of readiness to learn among Sunday school children in the GKI Klasis Waibu Moi, viewed from both physical and psychological dimensions. Data for this study were obtained through observation and interviews. Observation activities were conducted at GKI Diaspora Doyo Baru, GKI Yo Anibi, GKI Mahanai, and GKI Lahe Roi. Meanwhile, interview activities were conducted with representatives of Sunday school children, parents, and Sunday school teachers. The interview data collected were then subjected to reduction, classification, and analysis processes. The results of the study indicate that the readiness to learn among Sunday school children in GKI Klasisi Waibu, viewed from two dimensions, namely physical and psychological dimensions. The physical dimension includes the family's income level, education, career, and parental parenting patterns. Meanwhile, the psychological dimension includes interventions and cultural convergence and learning motivation reflected in the Sunday school curriculum, learning instruments, media, and learning resource